Identification and characterization of CircRNA-associated CeRNA networks in moso bamboo under nitrogen stress - Chenglei Zhu; Tingting Yuan; Kebin Yang; Yan Liu; Ying Li; Zhimin Gao (BMC Plant Biology, 2023)
Abstract Background Nitrogen is a macronutrient element for plant growth and development. Circular RNAs (circRNAs) serve as pivotal regulators for the coordination between nutrient supply and plant demand. Moso bamboo (Phyllostachys edulis) is an excellent plant with fast growth, and the mechanism of the circRNA-target module in response to nitrogen remains unclear. Results Deep small RNA sequencing results of moso bamboo seedlings under different concentrations of KNO3 (N0 = 0 mM, N6 = 6 mM, N18 = 18 mM) were used to identify circRNAs. A total of 549 circRNAs were obtained, of which 309 were generated from corresponding parental coding genes including 66 new ones. A total of 536 circRNA-parent genes were unevenly distributed in 24 scaffolds and were associated with root growth and development. Furthermore, 52 differentially expressed circRNAs (DECs) were obtained, including 24, 33 and 15 DECs from three comparisons of N0 vs. N6, N0 vs. N18 and N6 vs. N18, respectively. Based on integrative analyses of the identified DECs, differentially expressed mRNAs (DEGs), and miRNAs (DEMs), a competitive endogenous RNA (ceRNA) network was constructed, including five DECs, eight DEMs and 32 DEGs. A regulatory module of PeSca_6:12,316,320|12,372,905-novel_miR156-PH02Gene35622 was further verified by qPCR and dual-luciferase reporter assays. Conclusion The results indicated that circRNAs could participate in multiple biological processes as miRNA sponges, including organ nitrogen compound biosynthesis and metabolic process regulation in moso bamboo. Our results provide valuable information for further study of circRNAs in moso bamboo under fluctuating nitrogen conditions.